Impaired Production and Diurnal Regulation of Vascular RvDn-3 DPA Increase Systemic Inflammation and Cardiovascular Disease. Issue 6 (16th March 2018) - Colas, Romain A.; Souza, Patricia R.; Walker, Mary E.; Burton, Maudrian; Zasłona, Zbigniew; Curtis, Annie M.; Marques, Raquel M.; Dalli, Jesmond
Abstract : Rationale: : Diurnal mechanisms are central to regulating host responses. Recent studies uncovered a novel family of mediators termed as specialized proresolving mediators that terminate inflammation without interfering with the immune response. Objective: : Herein, we investigated the diurnal regulation of specialized proresolving mediators in humans and their role in controlling peripheral blood leukocyte and platelet activation. Methods and Results: : Using lipid mediator profiling and healthy volunteers, we found that plasma concentrations of n-3 docosapentaenoic acid-derived D-series resolvins (RvDn-3 DPA ) were regulated in a diurnal manner. The production and regulation of these mediators was markedly altered in patients at risk of myocardial infarct. These changes were associated with decreased 5-lipoxygenase expression and activity, as well as increased systemic adenosine concentrations. We also found a significant negative correlation between plasma RvDn-3 DPA and markers of platelet, monocyte, and neutrophil activation, including CD63 and CD11b. Incubation of RvDn-3 DPA with peripheral blood from healthy volunteers and patients with cardiovascular disease significantly and dose-dependently decreased platelet and leukocyte activation. Furthermore, administration of RvD5n-3 DPA to ApoE −/− (apolipoprotein E deficient) mice significantly reduced platelet–leukocyte aggregates, vascular thromboxane B2 concentrations, and aortic lesions. Conclusions: : These results demonstrate that peripheral blood RvDn-3 DPA are diurnally regulated in humans, and dysregulation in the production of these mediators may lead to cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.